Dual function Mg-doped binary metal ferrite: Photocatalytic degradation of trichlorophenol, bactericidal activity and molecular docking analysis - Mustafa, Faisal Suleiman; Oladipo, Akeem Adeyemi (Pergamon-Elsevier Science Ltd, 2023)
A new Mg-doped Zn0.5Ni0.5Fe2O4 (Mg-FZN) photocatalyst was synthesised using a simple co-precipitationdoping technique to develop a dual-function material with the ability to degrade hazardous and refractory pollutants and inactivate bacterial strains. The characterization results revealed that Mg-FZN is an n-type semiconductor with a conduction band of -0.413 eV, an average pore width of 2.32 nm, and a crystal size of 31.45 nm. The photocatalytic activity of Mg-FZN was assessed based on the degradation of 2,4,5-trichlorophenol and achieved 83.8% degradation efficiency under optimised conditions. The radical quenching results revealed that h+ significantly contributed to the photodegradation process while center dot OH, and center dot O-played key roles. Additionally, within 60 min, 25 mg of Mg-FZN had bactericidal effects on the bacteria E. coli and S. aureus in both the presence and absence of UV light. Mg-FZN showed H-bonding, electrostatic, and metal-contact interactions with the amino acid residues of the bacterial protein with high binding scores (-4.711 kcal/mol and -5.872 kcal/ mol), according to molecular docking.
Keywords: Photocatalysis; Mixed metal ferrites; Metal dopants; Chlorophenols; Bacteria time -kill